Two separate effects contribute to regulatory T cell defect in systemic lupus erythematosus patients and their unaffected relatives. (16th June 2017) - Costa, N.; Marques, O.; Godinho, S. I.; Carvalho, C.; Leal, B.; Figueiredo, A. M.; Vasconcelos, C.; Marinho, A.; Moraes‐Fontes, M. F.; Gomes da Costa, A.; Ponte, C.; Campanilho‐Marques, R.; et al.
Summary: Forkhead box P3 (FoxP3) + regulatory T cells (Tregs ) are functionally deficient in systemic lupus erythematosus (SLE), characterized by reduced surface CD25 [the interleukin (IL)‐2 receptor alpha chain]. Low‐dose IL‐2 therapy is a promising current approach to correct this defect. To elucidate the origins of the SLE Treg phenotype, we studied its role through developmentally defined regulatory T cell (Treg ) subsets in 45 SLE patients, 103 SLE‐unaffected first‐degree relatives and 61 unrelated healthy control subjects, and genetic association with the CD25‐encoding IL2RA locus. We identified two separate, uncorrelated effects contributing to Treg CD25. (1) SLE patients and unaffected relatives remarkably shared CD25 reduction versus controls, particularly in the developmentally earliest CD4 + FoxP3 + CD45RO – CD31 + recent thymic emigrant Tregs . This first component effect influenced the proportions of circulating CD4 + FoxP3 high CD45RO + activated Tregs . (2) In contrast, patients and unaffected relatives differed sharply in their activated Treg CD25 state: while relatives as control subjects up‐regulated CD25 strongly in these cells during differentiation from naive Tregs, SLE patients specifically failed to do so. This CD25 up‐regulation depended upon IL2RA genetic variation and was related functionally to the proliferation of activated Tregs, but not to their circulating numbers. Both effects were found related to T cell IL‐2 production. Our results point to (1) a heritable, intrathymic mechanism responsible for reduced CD25 on early Tregs and decreased activation capacity in an extended risk population, which can be compensated by (2) functionally independent CD25 up‐regulation upon peripheral Treg activation that is selectively deficient in patients. We expect that Treg ‐directed therapies can be monitored more effectively when taking this distinction into account. Abstract : FOXP3+ regulatory T‐cells (Tregs) are functionally deficient in Systemic Lupus Erythematosus (SLE) in connection to their deficient expression of the high‐affinity IL‐2 receptor CD25. We have identified two separate, uncorrelated effects contributing to reduced Treg CD25: (a) an early, heritable and apparently thymic effect shared by patients and unaffected relatives, and (b) deficient peripheral CD25 upregulation by activated Tregs restricted to the patients.